Biophysical and Dynamic Characterization of Fine-Tuned Binding of the Human Respiratory Syncytial Virus M2-1 Core Domain to Long RNAs - Caruso, Icaro P. [UNESP]; Guimarães, Giovana C. [UNESP]; Machado, Vitor B. [UNESP]; Fossey, Marcelo A. [UNESP]; Willbold, Dieter; Almeida, Fabio C.L.; Souza, Fátima P. [UNESP] (American Society for Microbiology, 2020)
The human respiratory syncytial virus (hRSV) M2-1 protein functions as a processivity and antitermination factor of the viral polymerase complex. Here, the first evidence that the hRSV M2-1 core domain (cdM2-1) alone has an unfolding activity for long RNAs is presented and the biophysical and dynamic characterization of the cdM2-1/RNA complex is provided. The main contact region of cdM2-1 with RNA was the α1-α2-α5-α6 helix bundle, which suffered local conformational changes and promoted the RNA unfolding activity. This activity may be triggered by base-pairing recognition. RNA molecules wrap around the whole cdM2-1, protruding their termini over the domain. The α2-α3 and α3-α4 loops of cdM2-1 were marked by an increase in picosecond internal motions upon RNA binding, even though they are not directly involved in the interaction. The results revealed that the cdM2-1/RNA complex originates from a fine-tuned binding, contributing to the unraveling interaction aspects necessary for M2-1 activity.
Keywords: Fine-tuned binding; HRSV M2-1 core domain; Molecular docking; Molecular dynamics; NMR; Nuclear magnetic resonance; RNA binding protein; RNA unfolding activity